Comportamento mecânico de implantes cone Morse com conicidade interna em 16° - Karam, Frederick Khalil (2020)
The aim of this study was answering some questions related to specific dental implants with Morse taper prosthetic connection. The main objective was to evaluate and compare the influence of inclination of internal taper (11.5° and 16°) on the abutment/implant interface and on the mechanical behavior of specific Morse taper implants. Thus, this study was didactically divided into three different chapters for the specific objectives. In Chapter 1, the mechanical behavior of 11.5° and 16° internal taper inclination and their respective titanium abutments was analyzed by Finite Element Analysis (FEA) and fatigue testing, following ISO 14801 standard. Fifty-four Morse taper implants were divided into six groups, varying implant, connection and macrogeometry. The computational tests for stress distribution (FEA) were performed and, then, the fatigue tests following the ISO 14801 standard. The results showed that independent of the macrogeometry of the implants, the system with 16° internal taper inclination was more resistant. In Chapter 2, fracture resistance and failure pattern tests were performed using a specific methodology. Twenty implants with their respective prosthetic abutments were divided into 2 groups, varying only the internal taper inclination. Subsequently, the implants were fixed, and the bending test was performed in a universal mechanical testing machine. Finally, the evaluation was performed to determine the failure pattern of the samples. The results indicate that the 16° system was statistically stronger when compared to the 11.5° system. In addition, samples from the 16° group tend to deform in the cervical region, while 11.5° samples tend to fracture in the middle third. In the third and last Chapter, the microscopic space between the interface implant/abutment was analyzed by comparing implants of different internal taper inclination (11.5° and 16°) using computed microtomography and microleakage with toluidine blue. Sixteen implants with open apex and their respective prosthetic abutments were divided into two groups, varying only the inclination of internal taper between them (11.5° and 16°) and installed in plastic tubes. Using a specific equipment developed by group, toluidine blue was applied to the apex of the implants and subsequently applied 2 bahr of pressure for 60 minutes. After the test, the samples were submitted to computed microtomography in order to evaluate if there was any microscopic space between the prosthetic abutment and the implant. It was not possible to observe toluidine blue extravasating the peri-implant region and could not find any image that would suggest microscopic space between implant and prosthetic abutment on computed tomography. Due to the results presented by the above chapters, it can be concluded that the 16° internal taper implant system has a higher resistance compared to 11.5° implants, regardless of macrogeometry. In addition, no microgaps was observed between the prosthetic abutment and implants in both systems studied, thus maintaining the biological sealing.